2022
DOI: 10.3390/nu14122373
|View full text |Cite
|
Sign up to set email alerts
|

Macronutrients Intake and Risk of Stomach Cancer: Findings from Case-Control Study

Abstract: Studies on the association between gastric cancer (GC) and the intake of nutrients in Jordan are very limited, while findings from other reports on the intake of energy and macronutrients are controversial. This study aimed to examine the associations between intake of energy and macronutrients and the risk of GC in a Jordanian population. A case-control study was carried out between March 2015 and August 2018 in four major hospitals, including an oncology center in Jordan. Study participants were 173 cases wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Subsequent studies confirmed the protective role of fiber on GC [12][13][14][15]. However, other authors did not find any association [16].…”
Section: Introductionmentioning
confidence: 89%
“…Subsequent studies confirmed the protective role of fiber on GC [12][13][14][15]. However, other authors did not find any association [16].…”
Section: Introductionmentioning
confidence: 89%